2004
DOI: 10.1158/1078-0432.ccr-04-1285
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor AP-2γ Is a Developmentally Regulated Marker of Testicular Carcinoma In situ and Germ Cell Tumors

Abstract: Purpose: Transcription factor activator protein-2␥ (TFAP2C, AP-2␥) was reported previously in extraembryonic ectoderm and breast carcinomas but not in the testis. In our recent gene expression study we detected AP-2␥ in carcinoma in situ testis (CIS, or intratubular germ cell neoplasia), precursor of testicular germ cell tumors. In this study we aimed to investigate the expression pattern of AP-2␥ and to shed light on this factor in germ cell differentiation and the pathogenesis of germ cell neoplasia.Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
142
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 46 publications
11
142
1
2
Order By: Relevance
“…18 Here, we show that CIS cells also express the miR-17-92 cluster, thus supporting earlier speculation that expression of miR-17-92 could be important for stem cell maintenance in the embryo. 9 In conclusion, our results indicate that miRNA downregulation of E2F1 mRNA translation is part of the normal spermatogenesis, protecting meiotic cells from apoptosis as modeled in Figure 1u.…”
supporting
confidence: 90%
“…18 Here, we show that CIS cells also express the miR-17-92 cluster, thus supporting earlier speculation that expression of miR-17-92 could be important for stem cell maintenance in the embryo. 9 In conclusion, our results indicate that miRNA downregulation of E2F1 mRNA translation is part of the normal spermatogenesis, protecting meiotic cells from apoptosis as modeled in Figure 1u.…”
supporting
confidence: 90%
“…This is consistent with recent reports on widespread expression of transcripts from both strands in large parts of the human genome (Kapranov et al, 2002;Cawley et al, 2004), and we speculate that this feature may contribute to the heterogeneity of overt tumours -especially N-SEMs. Even protein expression has earlier been reported to be markedly heterogeneous in TGCTs, including CIS (Rajpert-De Meyts et al, 1996;LifschitzMercer et al, 2002;Hoei-Hansen et al, 2004b;Kato et al, 2004). It is, however, evident from the RT -PCR results shown in Figure 2 that by combining results from a range of different genes, a TGCT sample could be classified as a SEM or N-SEM.…”
Section: Discussionmentioning
confidence: 90%
“…The undifferentiated EC and EC-derived cell lines have been more thoroughly investigated. A number of proteins highly expressed in EC are related to pluripotency, for example, POU5F1 (OCT-4) and TFAP2C (Hoei-Hansen et al, 2004b), and are equally highly expressed in SEM. It is important to remember that the genes we have identified here are differentially expressed between both CIS, SEM and N-SEM.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of AP-2γ were found in testicular cancer [18], germ cell tumours [18,19], advanced stages of ovarian cancer [20], and certain stages of melanoma [21]. In breast cancer, data mining of microarray expression studies has shown an association between high levels of TFAP2C mRNA and higher clinical grade and shorter survival times [17,22].…”
Section: Introductionmentioning
confidence: 99%